Diverse Macrophage Populations Contribute to the Inflammatory Microenvironment in Premalignant Lesions During Localized Invasion - Ibrahim, Ayman M.; Moss, Matthew A.; Gray, Zane; Rojo, Michelle D.; Burke, Caitlin M.; Schwertfeger, Kathryn L.; dos Santos, Camila O.; Machado, Heather L. (Frontiers in Oncology, 2020)
Myeloid cell heterogeneity remains poorly studied in breast cancer, and particularly in premalignancy. Here, we used single cell RNA sequencing to characterize macrophage diversity in mouse pre-invasive lesions as compared to lesions undergoing localized invasion. Several subpopulations of macrophages with transcriptionally distinct profiles were identified, two of which resembled macrophages in the steady state. While all subpopulations expressed tumor-promoting genes, many of the populations were highly pro-inflammatory, differing from reports in tumor-associated macrophages. Gene profiles of the myeloid cells were similar between early and late stages of premalignancy, although expansion of some subpopulations occurred. These results unravel macrophage heterogeneity in early progression and may provide insight into early intervention strategies that target macrophages.